Adult liver transplantation: UK clinical guideline - part 2: surgery and post-operation. Issue 5 (25th February 2020) - Millson, Charles; Considine, Aisling; Cramp, Matthew E; Holt, Andrew; Hubscher, Stefan; Hutchinson, John; Jones, Kate; Leithead, Joanna; Masson, Steven; Menon, Krish; Mirza, Darius; Neuberger, James; et al.
Abstract : Survival rates for patients following liver transplantation exceed 90% at 12 months and approach 70% at 10 years. Part 1 of this guideline has dealt with all aspects of liver transplantation up to the point of placement on the waiting list. Part 2 explains the organ allocation process, organ donation and organ type and how this influences the choice of recipient. After organ allocation, the transplant surgery and the critical early post-operative period are, of necessity, confined to the liver transplant unit. However, patients will eventually return to their referring secondary care centre with a requirement for ongoing supervision. Part 2 of this guideline concerns three key areas of post liver transplantation care for the non-transplant specialist: (1) overseeing immunosuppression, including interactions and adherence; (2) the transplanted organ and how to initiate investigation of organ dysfunction; and (3) careful oversight of other organ systems, including optimising renal function, cardiovascular health and the psychosocial impact. The crucial significance of this holistic approach becomes more obvious as time passes from the transplant, when patients should expect the responsibility for managing the increasing number of non-liver consequences to lie with primary and secondary care.